Production of quinomycin A in Streptomyces lasaliensis - Steinerová, N; Lipavská, H; Stajner, K; Cáslavská, J; Blumauerová, M; Cudlín, J; Vanĕk, Z (Folia microbiologica, 1987)
In addition to lasalocid, an oligoether coccidiostatic compound, other compounds are synthesized by Streptomyces lasaliensis. Mutants producing either of two antibiotics, lasalocid A or quinomycin A (an antibiotic of quinoxaline character), were obtained by natural selection and by mutagenesis. Methods of isolation, purification and estimation of both compounds were established.
Keywords: Quinoxalines; teplota; mutace; Mutation; chinoxaliny; Temperature; echinomycin; Echinomycin; Streptomyces